Work Discipline of Staff Nurses: The Role of Workload and Related Factors - Sondang Selviana; Tiarnida Nababan; Refi Ikhtiari (Indonesian Journal of Global Health Research, 2026)
This study aims to examine the work discipline of staff nurses: the role of workload and related factors at Royal Prima Hospital Jambi, including goals and abilities, leadership role modeling, compensation, disciplinary sanctions, and workload. The study employed a quantitative approach with a total of 55 staff nurse respondents. The results of the univariate analysis showed that most respondents had good work discipline (87.3%), good goals and abilities (87.3%), good leadership role modeling (87.3%), good compensation (81.8%), good disciplinary sanctions (89.1%), and moderate workload (61.8%). The bivariate analysis indicated significant relationships between goals and abilities, leadership role modeling, compensation, disciplinary sanctions, and workload with nurses’ work discipline (p < 0.05). Furthermore, multivariate analysis using logistic regression revealed that compensation was the most dominant factor associated with the work discipline of staff nurses (p = 0.003). The findings of this study conclude that improving the work discipline of staff nurses at Royal Prima Hospital Jambi is strongly influenced by compensation, in addition to leadership, competence, sanctions, and workload factors.